2012
DOI: 10.1590/s0001-37652012005000053
|View full text |Cite
|
Sign up to set email alerts
|

Leaf anatomy and its contribution to the systematics of Aechmea subgenus Macrochordion (de Vriese) Baker (Bromeliaceae)

Abstract: The leaf anatomy of the species Aechmea subgenus Macrochordion was analyzed to obtain valuable data on their taxonomic delimitation and to identify anatomical adaptations to their respective habitats and habits. All leaves of these species are hypostomatic, and present: peltate trichomes on both surfaces; stomata sunk in epidermal depressions; small epidermal cells with thick walls and inclusions of silica bodies; a mechanical hypodermis; an aquiferous parenchyma; chlorenchyma with fibrous clusters and air cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The information obtained through comparative morpho-anatomical studies is necessary for ecological, phylogenetic and evolutionary studies. For example, anatomical characters, especially of leaves, have been extensively used in the systematics of several plant families, including Bromeliaceae (De Faria et al, 2012), Myrtaceae (Al-Edany and Al-Saadi, 2012), Amaryllidaceae (Lin and Tan, 2015), Malpighiaceae (Araújo et al, 2010) and Asteraceae (Castro et al, 1997;Milan et al, 2006;Adedeji and Jewoola, 2008;Bombo et al, 2012;Akinnubi et al, 2014;Rojas-Leal et al, 2017;Lusa et al, 2018). Particularly in Asteraceae, leaf architecture and anatomical characters are extremely diverse (Bombo et al, 2012;Rojas-Leal et al, 2014, 2018 and have been studied from an ecological (Bercu et al, 2012;Moroney et al, 2013;Rivera et al, 2017;Ferraro and Scremin-Dias, 2018), physiological (Bondarev et al, 2003;McKown and Dengler, 2007;Santiago and Kim, 2009), and medical perspective (Cambi et al, 2006;Hulley et al, 2010;García-Sánchez et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The information obtained through comparative morpho-anatomical studies is necessary for ecological, phylogenetic and evolutionary studies. For example, anatomical characters, especially of leaves, have been extensively used in the systematics of several plant families, including Bromeliaceae (De Faria et al, 2012), Myrtaceae (Al-Edany and Al-Saadi, 2012), Amaryllidaceae (Lin and Tan, 2015), Malpighiaceae (Araújo et al, 2010) and Asteraceae (Castro et al, 1997;Milan et al, 2006;Adedeji and Jewoola, 2008;Bombo et al, 2012;Akinnubi et al, 2014;Rojas-Leal et al, 2017;Lusa et al, 2018). Particularly in Asteraceae, leaf architecture and anatomical characters are extremely diverse (Bombo et al, 2012;Rojas-Leal et al, 2014, 2018 and have been studied from an ecological (Bercu et al, 2012;Moroney et al, 2013;Rivera et al, 2017;Ferraro and Scremin-Dias, 2018), physiological (Bondarev et al, 2003;McKown and Dengler, 2007;Santiago and Kim, 2009), and medical perspective (Cambi et al, 2006;Hulley et al, 2010;García-Sánchez et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, considering the epidermal features on the adaxial layer, Ficus exasperata is distanced from F. muscuso and F. thonningii by having hypostomatic leaves. There exist studies [23][24][25][26][27][28] in which the positioning of stomata on the epidermal layer was used to delimit the taxa of plants. However, there is presently scarce information according to the literature on the discrimination of Ficus species based on the positioning of stomata but there is replete information on other epidermal indices such as stomatal types and epidermal cell shape [29].…”
Section: Discussionmentioning
confidence: 99%
“…The recent reports of the complete genomes of Ananas comosus (L.) Merr.) Versieux et al, 2010;De Faria, Vieira & Wendt, 2012;Magalhães & Mariath, 2012;Santos-Silva et al, 2013;Nogueira et al, 2015). Gilmartin & Brown, 1987;Varadarajan & Gilmartin, 1988).…”
Section: Evolution and Phylogeneticsmentioning
confidence: 99%
“…The use of morphological data in phylogenetic analysis decreased for many years before being re-established in the last decade, when micro-and macromorphological traits began to be employed at inter-and infrageneric levels (De Faria et al, 2004;Hornung-Leoni & Sosa, 2008;Almeida et al, 2009;Aguirre-Santoro et al, 2015;Da Costa et al, 2015;Donad ıo, Pozner & Giussani, 2015;Monteiro, Mantovani & Forzza, 2015;Saraiva, Mantovani & Forzza, 2015) and some studies in recent years have identified morphological characters with good taxonomic value for phylogenetic inferences (e.g. Versieux et al, 2010;De Faria, Vieira & Wendt, 2012;Magalhães & Mariath, 2012;Santos-Silva et al, 2013;Nogueira et al, 2015). In this issue, Kuhn et al (2016) present a study on morphoanatomical features of species of Tillandsioideae, revealing good systematic value of ovule morphology in delimiting genera in Tillandsioideae; its use in phylogenetic studies in this group should be tested.…”
Section: Evolution and Phylogeneticsmentioning
confidence: 99%